2017
DOI: 10.1007/s00382-017-3671-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal soil moisture and drought occurrence in Europe in CMIP5 projections for the 21st century

Abstract: Projections for near-surface soil moisture content in Europe for the 21st century were derived from simulations performed with 26 CMIP5 global climate models (GCMs). Two Representative Concentration Pathways, RCP4.5 and RCP8.5, were considered. Unlike in previous research in general, projections were calculated separately for all four calendar seasons. To make the moisture contents simulated by the various GCMs commensurate, the moisture data were normalized by the corresponding local maxima found in the outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
135
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 183 publications
(145 citation statements)
references
References 46 publications
7
135
0
3
Order By: Relevance
“…The SMI calculated from regional soil moisture simulations over the past 30 years indicated that such extreme drought affecting forest health was rare in Finland, and the summer drought in 2006 in southern Finland was the most severe one in the 30 year study period (Gao et al, 2016). According to climate scenarios, regardless of the anticipated increase in precipitation, a modest drying of soil is foreseen in northern Europe during the 21st century because of intensifying evapotranspiration (Ruosteenoja et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The SMI calculated from regional soil moisture simulations over the past 30 years indicated that such extreme drought affecting forest health was rare in Finland, and the summer drought in 2006 in southern Finland was the most severe one in the 30 year study period (Gao et al, 2016). According to climate scenarios, regardless of the anticipated increase in precipitation, a modest drying of soil is foreseen in northern Europe during the 21st century because of intensifying evapotranspiration (Ruosteenoja et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This was not the case under severe climate warming (RCP8.5), which decreased the share of Norway 415 spruce (opposite to birch) in southern Finland compared to the current climate because growing 416 conditions became sub-optimal for Norway spruce (see Ruosteenoja et al 2017). Under a severe 417 climate warming, the predicted amount of damage was largest in southern Finland when the planting 418 of birch increased.…”
Section: Discussion and Conclusion 389mentioning
confidence: 99%
“…This was not evident based on earlier impact studies employing climate data of the CMIP3 database. Climate change likely also increases abiotic and biotic damages (e.g., [57][58][59][60][61]), which may partially counteract the positive effects of climate change on forest growth and timber supply (e.g., [62,63]). However, we did not consider them in our study.…”
Section: Discussionmentioning
confidence: 99%